Estudo comparativo de parâmetros microbiológicos do solo relacionados ao ciclo do carbono em sistemas de produção na Amazônia Mato-Grossense - Lima, Daniel Dias de (2023)
The organization of agricultural production across different production systems plays a crucial role in ensuring sustainable food production, influencing soil carbon sequestration, and mitigating the effects of the greenhouse effect. This study aimed to assess the impact of production systems on Microbial Biomass Carbon (MBC), Total Organic Carbon (TOC), and Microbial Quotient (Qmic) levels, as well as to compare the potential for atmospheric carbon sequestration between integrated and exclusive production systems. The experimental design was in randomized blocks in an experiment conducted at Embrapa Agrossilvipastoril in Sinop, MT. The representative crops for each system were: Forest (F); Crop (L), Livestock (P), Livestock-Crop Integration (IPL); Crop-Livestock Integration (ILP); and Crop-Livestock-Forestry Integration (ILPF). The crops representing each system were the succession Glycine max and Zea mays, Urochloa brizantha cv. Marandu, and Eucalyptus urograndis. The results revealed that the production system had an impact on the levels of MBC and TOC in the soil. The Crop (L) system exhibited higher values of Carbon from Microbial Biomass and Microbial Quotient, while Livestock (P) system showed higher values of Total Organic Carbon. No significant statistical difference was observed in the Total Organic Carbon values between the integrated and exclusive production systems.